Early Transcriptional Changes Induced by Wnt/β-Catenin Signaling in Hippocampal Neurons - Eduardo Pérez-Palma; Víctor Andrade; Mario O. Caracci; Bernabé I. Bustos; Camilo Villaman; Matías A. Medina; Miguel E. Ávila; Giorgia D. Ugarte; Giancarlo V. De Ferrari (Neural Plasticity)
Wnt/β-catenin signaling modulates brain development and function and its deregulation underlies pathological changes occurring in neurodegenerative and neurodevelopmental disorders. Since one of the main effects of Wnt/β-catenin signaling is the modulation of target genes, in the present work we examined global transcriptional changes induced by short-term Wnt3a treatment (4 h) in primary cultures of rat hippocampal neurons. RNAseq experiments allowed the identification of 170 differentially expressed genes, including known Wnt/β-catenin target genes such as Notum, Axin2, and Lef1, as well as novel potential candidates Fam84a, Stk32a, and Itga9. Main biological processes enriched with differentially expressed genes included neural precursor (GO:0061364, p-adjusted = 2.5 × 10−7), forebrain development (GO:0030900, p-adjusted = 7.3 × 10−7), and stem cell differentiation (GO:0048863 p-adjusted = 7.3 × 10−7). Likewise, following activation of the signaling cascade, the expression of a significant number of genes with transcription factor activity (GO:0043565, p-adjusted = 4.1 × 10−6) was induced. We also studied molecular networks enriched upon Wnt3a activation and detected three highly significant expression modules involved in glycerolipid metabolic process (GO:0046486, p-adjusted = 4.5 × 10−19), learning or memory (GO:0007611, p-adjusted = 4.0 × 10−5), and neurotransmitter secretion (GO:0007269, p-adjusted = 5.3 × 10−12). Our results indicate that Wnt/β-catenin mediated transcription controls multiple biological processes related to neuronal structure and activity that are affected in synaptic dysfunction disorders.